Examining Differential Item Functioning: IRT-Based Detection in the Framework of Confirmatory Factor Analysis. (3rd July 2017) - Dimitrov, Dimiter M.
ABSTRACT: This article offers an approach to examining differential item functioning (DIF) under its item response theory (IRT) treatment in the framework of confirmatory factor analysis (CFA). The approach is based on integrating IRT- and CFA-based testing of DIF and using bias-corrected bootstrap confidence intervals with a syntax code in Mplus.